PEMIKIRAN POLITIK MAHMÛD SYALTÛT - Amin Husein Nasution (State Islamic University North Sumatra, 2009)
Abstract: The Political Thought of Mahmûd Syaltût. The emergence of the Western political ideas in the Muslim world marks the beginning of the 20th century Islamic political thought. On the main, there are at least three mainstreams of attitude demonstrated by Islamic political thinkers as a response to such Western ideas, namely to accept in its entirety, to refuse and to criticize. The author argues that Mahmûd Syaltût is one of the political thinkers who belongs to the third category and tries to appreciate the positive aspects of Western political thought but who still sticks to the injunctions of the Qur’an and prophetic traditions. This paper tries to analyze the political thought of Mahmûd Syaltût how it originated and developed.Kata Kunci: syura, sosialisme-religius,